Pemodelan Strategi Pemasaran Digital untuk Wisata Bahari Berkelanjutan dengan Pendekatan SWOT-AHP dan Porter's Five Forces Model - Fathorrozi Ariyanto; Doni Ferdiansyah; Aang Kisnu Darmawan (LPPM STMIK IKMI Cirebon, 2025)
This study aims to develop a sustainable digital marketing strategy model for marine tourism in Indonesia. The SWOT-AHP approach is used to identify and prioritize internal and external factors affecting the sector. Porter's Five Forces and Diamond Model analyses are applied to understand the competitive landscape and competitive advantages of Indonesia. The results of the SWOT-AHP analysis indicate that internal strengths and untapped marine tourism potential are dominant factors. The recommended digital marketing strategies are educational and conservation content marketing (priority 0.555), social media community building (0.265), SEO/SEM (0.118), and influencer marketing (0.062). Porter's Five Forces analysis highlights the importance of differentiation, building strong customer relationships, transparency, collaboration, and innovation. The Diamond Model analysis emphasizes the importance of utilizing natural resources, improving the quality of human resources, developing knowledge and technology, strengthening infrastructure, and collaborating with stakeholders. This study makes a significant contribution by providing a comprehensive and sustainable digital marketing strategy model for marine tourism in Indonesia. This model integrates SWOT-AHP analysis, Porter's Five Forces, and the Diamond Model, and considers economic and environmental sustainability objectives. The findings can help stakeholders develop responsible marketing strategies and promote sustainable tourism in Indonesia, driving economic growth while preserving the beauty and biodiversity of the sea.